Pilates workouts can improve the labor and newborn outcomes: A case control study - Kırıcı, Pınar; Nacar, Mehmet Can; Karaçor, Talip; Bülbül, Mehmet; Baktıroğlu, Merve; Mavral, Nihal; Kaya, Necla (Journal of Surgery and Medicine, 2021)
Background/Aim: Physical activity during pregnancy assumes an important role in the health of both the pregnant and newborn. Our study aims to evaluate the effects of Pilates workouts on labor and newborn outcomes. Methods: This retrospective case control study was conducted with the nulliparous pregnant women admitted to our obstetrics clinic. We evaluated the effects of a Pilates workout program for 70-80 minutes per day, once a week for eight weeks, on the labor and newborn outcomes. We defined the labor outcomes as the type of delivery and the gestational age at delivery and the newborn outcomes as one-minute (APGAR-1) and five-minute Apgar scores (APGAR-5). Results: The incidences of episiotomy, vacuum-assisted vaginal delivery, and cesarean section (CS) were significantly lower in pregnant women who participated in Pilates workouts (P<0.001). Pilates workouts increased the chance of normal vaginal delivery. The gestational age at delivery was significantly lower, and the APGAR-1 and APGAR-5 scores were significantly higher among those in the Pilates group (P<0.001). Conclusion: A supervised Pilates workout is an effective and achievable exercise method decreasing cesarean delivery and assisted vaginal delivery. It also has no negative effects on newborns, supported by the higher APGAR scores of babies whose mothers were in the Pilates group.